2015
DOI: 10.1007/s40429-015-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging in Gambling Disorder

Abstract: Gambling disorder recently was reclassified under the category “substance-related and addictive disorders.” With regard to the diagnostic criteria, it overlaps a great deal with substance use disorder, i.e., loss of control, craving/withdrawal, and neglect of other areas of life. However, the gambling disorder symptom “chasing one’s losses” is the only criterion absent from substance use disorder. Therefore, special forms of reward (i.e., gain/loss) processing, such as the processing of loss avoidance and loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 114 publications
1
8
0
1
Order By: Relevance
“…However, our study is innovative because we have directly compared an SUD and a behavioral addictive disorder and we have used an extensive set of tools to investigate the neural correlates of reduced LA in PG and AD. Disentangling the psychological from the neurotoxic factors of addiction is one of the great challenges of current neurobehavioral research 73 . Further comparative and transdiagnostical studies like ours are needed to find neurobehavioral markers for etiology research, for better diagnosis and better measurement of treatment success 3 , 74 – 77 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our study is innovative because we have directly compared an SUD and a behavioral addictive disorder and we have used an extensive set of tools to investigate the neural correlates of reduced LA in PG and AD. Disentangling the psychological from the neurotoxic factors of addiction is one of the great challenges of current neurobehavioral research 73 . Further comparative and transdiagnostical studies like ours are needed to find neurobehavioral markers for etiology research, for better diagnosis and better measurement of treatment success 3 , 74 – 77 .…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature has shown that chasing represents an important step in the development and maintenance of gambling disorder (Breen & Zuckerman, 1999;Goudriaan, Yücel, & van Holst, 2014;Lesieur, 1984; see also Corless & Dickerson, 1989;Sharpe, 2002; for a review, see Nigro, Ciccarelli, & Cosenza, 2018b), and is one of the few observable signs for disordered gambling (Gainsbury, Suhonen, & Saaststamoinen, 2014), and the only criterion of gambling addiction absent in substance use disorder (Quester & Romanczuk-Seiferth, 2015). Prior research found that chasing is associated, among others, with impulsivity (Breen & Zuckerman, 1999), sensation seeking (Linnet, Røjskjaer, Nygaard, & Maher, 2006), increased activation in brain regions related to reward expectation (Campbell-Meiklejohn et al, 2008), low sensitivity to punishment (Kim & Lee, 2011), poor decision-making (Nigro et al, 2018a), disinhibition (Nigro et al, 2018b), alexithymia (Bibby, 2016), and shortened time horizon .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the involvement of undersensitivity to losses in potentially problematic gambling behaviors is already well known. Abnormal reaction to losses discriminates between gamblers and other addicted patients ( Torres et al., 2013 ), and some studies have also shown pathological and frequent gamblers to have lower scores in punishment sensitivity as measured by self-reports ( Goudriaan, Oosterlaan, de Beurs, & van den Brink, 2004 ; Navas et al., 2014 ) and an abnormal brain response to monetary losses (see Quester & Romanczuk-Seiferth, 2015 , for a review). Relatedly, loss processing has also been shown to be involved in gambling-related distorted cognitions ( Billieux, Van der Linden, Khazaal, Zullino, & Clark, 2012 ; Michalczuk, Bowden-Jones, Verdejo-Garcia, & Clark, 2011 ; Worhunsky, Malison, Rogers, & Potenza, 2014 ).…”
Section: Introductionmentioning
confidence: 99%